The effect of islamic corporate social responsibility, corporate zakat, liquidity and company on financial performance of sharia banks - Friscilia Junike Aryawati; Nafis Irkhami (Islamic Accounting Journal, 2022)
This study aims to examine and determine the effect of Islamic Corporate Social Responsibility (ICSR), corporate zakat and liquidity on the financial performance of Islamic banking. In addition, this study also aims to examine whether the variable size of the company moderates the relationship between each variable Islamic Corporate Social Responsibility (ICSR), corporate zakat and liquidity on the financial performance of Islamic banking. The sample used in this study is Islamic commercial banks listed at the OJK for the 2016-2020 period. The total sample is 9 Islamic commercial banks using purposive sampling. The data used are secondary data, the analytycal method used is panel data regression analysis with a Moderated Regression Analysis (MRA) test using data processing software Eviews 9. The results show that partially Islamic Corporate Social Responsibility (ICSR) has a negative and significant effect on financial performance as measured by ROA, corporate zakat has a negative and insignificant effect on financial performance as measured by ROA, liquidity as measured by the Current Ratio (CR) has an effect negative and insignificant to financial performance as measured by ROA. The results of research related to moderating variables show that company size is able to moderate the relationship between ICSR and financial performance, company size has no effect as a moderating variable between company zakat and financial performance and company size has no effect as a moderating variable between liquidity and performance.Keywords: Islamic Corporate Social Responsibility (ICSR), corporate zakat, liquidity, company size, financial performance.